Ethno-Eco-Design for ‘Literapreneurship’ in Screen Printing in Semarang - Eko Sugiarto; Kemal Budi Mulyono; Bangkit Sanjaya; Muh Fakhrihun Naam; Retnoningrum Hidayah; Arif Fiyanto (Catharsis, 2025)
This study explores the concept of Ethno-Eco-Design as a strategic approach to empower literapreneur start-ups in the screen printing and apparel industry in Semarang. Based on preliminary surveys and related studies, these start-ups face two major challenges in 21st-century entrepreneurship: low ecological awareness in their production and business practices, and limited market segmentation, particularly in reaching millennial consumers. Using a participatory action research method, this study examines how the integration of local cultural elements (ethno-design) with environmentally friendly design practices (eco-design) can enhance the sustainability and market relevance of these start-ups. As a result, a design framework was developed that not only supports green entrepreneurship (ecopreneurship) but also expands the literacy and creative capacity of young business actors in a competitive and environmentally conscious market.